2011
DOI: 10.21608/jpp.2011.85503
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Two Promising Sugar Cane Varieties Under Different Harvesting Dates

Abstract: Tow field experiments were carried out at Mallawi Agricultural Research Station, Minia Governorate grown as plant cane in 2008/2009 and 2009/2010 seasons and the 1 st ratoon crops in 2009/2010 to investigate three harvest dates at ages of (10, 12 and 14 months) on the performance of two promising sugar cane varieties G.99-80, G.99-160 and the commercial variety G.T.54-9 as a control. A split plot design with four replications was used in both seasons. Harvest dates treatments were allocated in the main plots w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
5
7
0
Order By: Relevance
“…Such effect might be attributed to demonstrate that there was a substantial amount of growth in terms of cane stalk height at the end of harvesting ages for the promising varieties. These results are in accordance with those obtained by Ahmed (2003); Osman et al (2011);El-Geddawy et al (2012) and Hagos et al (2014) they reported that Stalk height was significantly affected by harvesting age.…”
Section: Stalk Heightsupporting
confidence: 92%
See 3 more Smart Citations
“…Such effect might be attributed to demonstrate that there was a substantial amount of growth in terms of cane stalk height at the end of harvesting ages for the promising varieties. These results are in accordance with those obtained by Ahmed (2003); Osman et al (2011);El-Geddawy et al (2012) and Hagos et al (2014) they reported that Stalk height was significantly affected by harvesting age.…”
Section: Stalk Heightsupporting
confidence: 92%
“…These results are in accordance with those obtained by Kumara and Bandara (2002); Ahmed (2003); Amolo, et. al., (2006) and Osman et. al., (2011) they harvest dates significantly differed in sugar recovery percentage.…”
Section: Sugar Recovery Percentagementioning
confidence: 97%
See 2 more Smart Citations
“…This indicates that these genotypes had accumulated favorable alleles for tallness and could be used in future breeding programs. Ahmed (2003), Osman et al (2011), Hagos et al (2014 and Ahmed et al (2016 a) reported that delay harvesting date up to 14 months gave the highest values of stalk height in plant-cane and 1stratoon-crops.…”
Section: A1-stalk Lengthmentioning
confidence: 97%